2017
DOI: 10.1111/1471-0528.15004
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of seminal plasma in in vitro fertilisation treatment: a systematic review and meta‐analysis

Abstract: SP at the time of oocyte pickup is associated with higher CPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Another possibility could be that this protein has a direct impact on conceptus. In this sense, SP has been reported to exert a positive effect on pregnancy outcomes, specifically improving implantation and pregnancy rates in humans ( Crawford et al, 2015 ; Saccone et al, 2019 ) and even modifying embryo gene expression in pigs ( Martinez et al, 2020 ). Thus, it cannot be discarded the influence of SP-AKR1B1 on the improvement of embryo survival and even implantation, through the modulation of the uterine environment.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility could be that this protein has a direct impact on conceptus. In this sense, SP has been reported to exert a positive effect on pregnancy outcomes, specifically improving implantation and pregnancy rates in humans ( Crawford et al, 2015 ; Saccone et al, 2019 ) and even modifying embryo gene expression in pigs ( Martinez et al, 2020 ). Thus, it cannot be discarded the influence of SP-AKR1B1 on the improvement of embryo survival and even implantation, through the modulation of the uterine environment.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents and swine, seminal plasma exposure mediates ovarian function by increasing progesterone synthesis or altering immune cells within the corpus luteum (Gangnuss et al 2004. Unprotected intercourse at the time of embryo transfer, or seminal plasma exposure during IVF treatment increases clinical pregnancy rates in women (Tremellen et al 2000, Saccone et al 2019. It is unclear if seminal plasma can facilitate the same effect on pregnancy success in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Some meta-analyses provided additional information about seminal plasma in clinical pregnancy rates. The meta-analysis conducted by Crawford and collaborators [ 190 ] demonstrated a significant improvement in clinical pregnancy rates, approximately 23%, while Saccone and collaborators demonstrate a 20% improvement [ 191 ]. However, other authors’ analysis concluded that seminal plasma may effectively increase clinical pregnancy rates, but the finding should be regarded with caution since there is not enough evidence to determine the impact on live births [ 192 ].…”
Section: Role Of Seminal Plasma On Fertility Techniques and Importance Of Its Antioxidants In The Female Reproductive Tractmentioning
confidence: 99%